Instagram: Platform Pemasaran Inovatif Bagi Pedagang Informal Di Jakarta - Nia Sonani (Journal of Economic, Bussines and Accounting (COSTING), 2022)
Social networks in marketing are unavoidable for companies that need excellence. This study explores how informal traders in Jakarta use Instagram as a marketing tool because most of the available literature focuses on small businesses. Screenshots of 30 Instagram accounts were taken, downloaded for data collection, and then triangulated with five interviews with informal traders. The findings show that informal merchants gain new customers on Instagram through creating their accounts, renting space on agent accounts, and disrupting comments on posts. In addition, informal merchants promote their business by posting products, testimonials from satisfied customers and aligning advertising messages with attractive images/photos that attract traffic attention. These findings imply the need for informal traders' social media marketing training and awareness. Keywords: Instagram, social network, company, informal trader.